Synthesis of Cyclopropane Fatty Acids by C(sp3)−C(sp3) Cross‐Coupling Reaction and Formal Synthesis of α‐Mycolic Acid. Issue 19 (14th August 2018) - Iwasaki, Takanori; Terahigashi, Shohei; Wang, Yufei; Tanaka, Arisa; Zhao, Hanqing; Fujimoto, Yukari; Fukase, Koichi; Kambe, Nobuaki
Abstract: An iterative Ni‐catalyzed C( sp 3 )−C( sp 3 ) cross‐coupling reaction of a novel cis ‐cyclopropane containing bifunctional building blocks with alkyl halides and alkyl Grignard reagents enabled the introduction of a cyclopropane ring into the desired position(s) of saturated carbon frameworks, providing a straightforward synthetic route to cyclopropane fatty acids. The present method creates a direct route for the construction of saturated carbon frameworks, and can avoid the tedious multistep operations based on unsaturated functional group manipulations that are often employed in conventional synthetic routes. This method could be applicable to the synthesis of trans ‐cyclopropane fatty acids and enantioenriched cyclopropane fatty acids. Formal synthesis of α‐mycolic acid was achieved by the C( sp 3 )−C( sp 3 ) cross‐coupling reaction of cyclopropane‐containing bifunctional building blocks. Abstract :